Green Microfluidic Method for Sustainable and High-Speed Analysis of Basic Amino Acids in Nutritional Supplements - Iva Pukleš; Csilla Páger; Nikola Sakač; Bojan Šarkanj; Dean Marković; Marija Kraševac Sakač; Marija Jozanović (Molecules)
Amino acids (AAs) have broad nutritional, therapeutic, and medical significance and thus are one of the most common active ingredients of nutritional supplements. Analytical strategies for determining AAs are high-priced and often limited to methods that require modification of AA polarity or incorporation of an aromatic moiety. The aim of this work was to develop a new method for the determination of L-arginine, L-ornithine, and L-lysine on low-cost microchip electrophoresis instrumentation conjugated with capacitively coupled contactless conductivity detection. A solution consisting of 0.3 M acetic acid and 1 × 10−5 M iminodiacetic acid has been identified as the optimal background electrolyte, ensuring the shortest possible analysis time. The short migration times of amino acids (t ≤ 64 s) and method simplicity resulted in high analysis throughput with high precision and linearity (R2<semantics>≥</semantics> 0.9971). The limit of detection values ranged from 0.15 to 0.19 × 10−6 M. The accuracy of the proposed method was confirmed by recovery measurements. The results were compared with CE-UV-VIS and HPLC-DAD methods and showed good agreement. This work represents the first successful demonstration of the ME-C4D analysis of L-arginine, L-ornithine, and L-lysine in real samples.